2017
DOI: 10.18632/oncotarget.19489
|View full text |Cite
|
Sign up to set email alerts
|

MiR-23a targets RUNX2 and suppresses ginsenoside Rg1-induced angiogenesis in endothelial cells

Abstract: Rg1 is a predominant protopanaxatriol-type of ginsenoside found in Panax ginseng, and it has been shown to have anti-cancer effects in multiple types of cancer cells. However, Rg1 also induces the expression of proangiogenic factors, such as vascular endothelial growth factor (VEGF-A), in endothelial cells. Unfortunately, angiogenesis positively correlates with cancer development. In this study, we identified RUNX2 as a regulator of ginsenoside Rg1-induced angiogenesis for the first time. We found that RUNX2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…New research has found that lyophilized PRF can mediate Runx2enhanced craniofacial bone regeneration (Li et al, 2014). Furthermore, Rg1 can stimulate human umbilical vein endothelial cells to undergo angiogenesis via the miR-23a/ RUNX2/VEGF-A pathway (Wu et al, 2017). Therefore, key factors, such as the presence of bone tissue components in the "adipose tissue block" induced by PRF and Rg1 and the correlation between Runx2 expression in transplanted adipose stem cells and tumor formation, must be clarified before clinical trials.…”
Section: Rg1 Regulates the Proliferation And Differentiation Of Mscsmentioning
confidence: 99%
“…New research has found that lyophilized PRF can mediate Runx2enhanced craniofacial bone regeneration (Li et al, 2014). Furthermore, Rg1 can stimulate human umbilical vein endothelial cells to undergo angiogenesis via the miR-23a/ RUNX2/VEGF-A pathway (Wu et al, 2017). Therefore, key factors, such as the presence of bone tissue components in the "adipose tissue block" induced by PRF and Rg1 and the correlation between Runx2 expression in transplanted adipose stem cells and tumor formation, must be clarified before clinical trials.…”
Section: Rg1 Regulates the Proliferation And Differentiation Of Mscsmentioning
confidence: 99%
“…Reduced TSGA10 expression led to the growth, migration, and tube formation of the vascular endothelial cells [50]. Wu et al showed that miR-23a might also suppress the expression of the vascular endothelial growth factor A (VEGF-A), by targeting its translational facilitator RUNX2 in the vascular endothelial cells [116].…”
Section: Biological Role Of the Mir-23a In Human Cancermentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a group of single‐strand noncoding RNAs with around 23 nucleotides, reputed to bring about posttranscriptional inhibition on gene expression by targeting the 3′‐untranslated regions (3′UTRs) of mRNAs . Dysregulation of miRNAs could lead to diverse disorders such as cancer, and the oncogenic or tumor suppressive roles of miRNAs vary according to the type of mRNAs they target . miR‐488‐3p has been newly discovered to be a tumor suppressor in several cancers, such as in glioma, and melanoma .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Dysregulation of miRNAs could lead to diverse disorders such as cancer, and the oncogenic or tumor suppressive roles of miRNAs vary according to the type of mRNAs they target. [10][11][12][13][14] miR-488-3p has been newly discovered to be a tumor suppressor in several cancers, such as in glioma, 15 and melanoma. 16 However, never has the role of miR-488-3p been explored in ESCC.…”
Section: Introductionmentioning
confidence: 99%